Local structure and superconductivity in (Bi1.6Pb0.4Sr2Ca2Cu3O10+δ)1-x(Fe3O4)x compounds. Issue 12 (15th June 2021) - Tran, Dzung T.; Pham, An T.; Pham, Ha H.; Nguyen, Nhung T.; Nam, Nguyen H.; Man, Nguyen K.; Kang, Won-Nam; Hsu, I-Jui; Klysubun, Wantana; Tran, Duc H.
Abstract: In this work, a close correlation between variations of critical temperature (Tc ) and the hole concentration of (Bi1.6 Pb0.4 Sr2 Ca2 Cu3 O10+δ )1-x (Fe3 O4 )x systems was studied. The (Bi1.6 Pb0.4 Sr2 Ca2 Cu3 O10+δ )1-x (Fe3 O4 )x samples were fabricated using the solid-state reaction method, where x ranged from 0 to 0.2. The Tc values of the samples deduced from magnetization versus temperature measurement gradually decreased with increasing the Fe3 O4 content (x). To investigate a possible reason for the observed decrease in the values of Tc in the samples, the valence state of copper (V) and the hole concentration (p) in all samples were examined by analyzing the Cu K-edge and Cu L2, 3 -edge X-ray absorption near edge structure (XANES) spectra. The values of V and p monotonously decreased with the increase in Fe3 O4 doping content (x) and agreed with the behavior of Tc . The existence of Fe 3+ was confirmed by analyzing Fe L2, 3 -edge XANES. Hence, Fe 3+ ions possibly entered the lattice structure of the samples and filled the holes in CuO2 planes. The degradation of superconductivity in Fe3 O4 doped samples was then explained.